A meta-analysis of the public-private partnership literature reviews: exploring the identity of the field - Narbaev, Timur (International Journal of Strategic Property Management, 2022)
The growing literature in PPP has made the field multi-disciplinary, over-differentiated, and unconsolidated. Taking a meta-analysis lens, this study investigates an unexplored identity of the field. It consolidates 61 review articles in PPP, analyses them across numerous review categories, and provides implications and suggestions for future studies. The review categories include the purpose of study, methods used, dataset details, journal and author details, primary disciplinary focus, awareness of previous review studies, and evolution of the PPP review literature. The findings reveal that the literature progressed through four evolution phases: from initiation, formation, growth, to expansion. Future review works should involve more empirical studies and examine the practical relevance of the PPP research. Promising areas are PPP governance, complexity, post-transfer phases, sustainability-related issues, and real estate development through PPP. The PPP researchers in construction engineering and management, property management, public management, and transportation will benefit from understanding the field’s identity, how it is currently being formed, promising areas, and where the literature is evolving.